Carbonized metal-organic frameworks nanorods as recyclable photocatalyst for visible light-induced water oxidation - Zhang, Min.; Jianmin, Luo.; Liang, Xiaoyu.; Yan, Baolin.; Baikenov, M.I.; Su, Xintai.; Chi, Le.; Yang, Chao. (Elsevier Science BV, 2018)
Magnetic Fe2C nanorods were successfully synthesized by the carbonization of iron-based metal–organic framework (MOF) template and examined as photocatalyst for water oxidation reaction. An apparent turnover frequency (TOF) of 2.73 103 s 1 and oxygen yield of 20.64% were obtained with Fe2C in an alkalescent aqueous solution. The rod-like Fe2C materials is convenient to recovery and recycling of the catalyst for water oxidation. The surface conditions of the Fe2C also remain unchanged after the photocatalytic reaction, as confirmed by X-ray photoelectron spectroscopy (XPS). Our work demonstrates that Fe2C as efficient WOCs is a promising candidate for water oxidation.
Keywords: Fe2C nanorods; Carbonization; MOF template; Water oxidation; Recovery